2017
DOI: 10.1093/ons/opx190
|View full text |Cite
|
Sign up to set email alerts
|

Deep Temporal Nerve Transfer for Facial Reanimation: Anatomic Dissections and Surgical Case Report

Abstract: The middle deep temporal branches can be readily identified and utilized for facial reanimation. This technique provided a successful reanimation of upper facial muscles with independent activation. Utilizing multiple sources for neurotization of the facial muscles, different potions of the face can be selectively reanimated to reduce the risk of synkinesis and improved control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The studies did a total of 123 dissections on 66 cadavers 6 , 7 , 8 , 9 , 11 (of which 2 unpreserved dissections 11 ) and 6 clinical operations. 2 , 10 Landmarks used were the infratemporal fossa (IFT), 7 , 8 , 9 infratemporal crest (ITC), 7 posterior deep temporal artery (PDTA), 7 zygomatic arch (ZA), 3 , 6 , 8 , 11 TM, 3 , 8 superior head of lateral pterygoid muscle (LPM), 9 jugal point (JP) 10 and the tragus. 6 , 11 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies did a total of 123 dissections on 66 cadavers 6 , 7 , 8 , 9 , 11 (of which 2 unpreserved dissections 11 ) and 6 clinical operations. 2 , 10 Landmarks used were the infratemporal fossa (IFT), 7 , 8 , 9 infratemporal crest (ITC), 7 posterior deep temporal artery (PDTA), 7 zygomatic arch (ZA), 3 , 6 , 8 , 11 TM, 3 , 8 superior head of lateral pterygoid muscle (LPM), 9 jugal point (JP) 10 and the tragus. 6 , 11 …”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, five were cadaveric studies 6 , 7 , 8 , 9 , 11 , one clinical 2 and one a combination of a cadaveric study and a case report 10 . The studies did a total of 123 dissections on 66 cadavers 6 , 7 , 8 , 9 , 11 (of which 2 unpreserved dissections 11 ) and 6 clinical operations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique may reanimate the facial muscles with independent activation. 12 Experimentally, biodegradable metallic magnesium filaments, placed inside hollow nerve conduits, supported nerve repair by providing contact guidance support for axonal regeneration. With a nerve gap of 6 mm and 6 weeks post-repair, magnesium filaments had partially resorbed.…”
Section: Discussionmentioning
confidence: 99%
“…Facial movements are observed as early as 4 months postoperatively and good facial function is usually achieved in about 12 months (Biglioli et al, 2017 ; Murphey et al, 2018 ). Alternatively, the middle deep temporal branches of the trigeminal nerve were recently proposed for facial reanimation, providing successful upper facial muscle reanimation with independent activation (Dauwe et al, 2016 ; Mahan et al, 2018 ). In the current review, we identified this technique after GTR of VS using the TRL approach by Hardy et al ( 1989 ; Table 3 ).…”
Section: Systematic Review Of the Literaturementioning
confidence: 99%